First‐time events between parents and preterm infants are affected by the designs and routines of neonatal intensive care units. (2nd August 2014) - Baylis, Rebecca; Ewald, Uwe; Gradin, Maria; Hedberg Nyqvist, Kerstin; Rubertsson, Christine; Thernström Blomqvist, Ylva
Abstract Aim Early parental bonding with preterm babies is particularly important, and the aim of our study was to explore when parents experienced what they regarded as important events for the first time while their infant was in the neonatal intensive care unit (NICU). Methods The study was part of a longitudinal project on Kangaroo Mother Care at two Swedish university hospitals. The parents of 81 infants completed questionnaires during their infants' hospital stay. Results Most parents saw and touched their infants immediately after birth, but only a few could hold them skin to skin or swaddle them. Other important events identified by parents included the first time they performed care giving activities and did so independently, interaction and closeness with the infant, signs of the infant's recovery and integration into the family. The timing of the events depended on the physical design of the NICU, whether parents' could stay with their infant round‐the‐clock and when they were allowed to provide care under supervision and on their own. Conclusion The design and routines of the NICU dictated when parents first interacted with their infants. Clinical guidelines that facilitate early contact with preterm babies can help parents to make the transition to their parental role.